Multi-emission luminescence dating of heated chert from the Middle Stone Age sequence at Sodmein Cave (Red Sea Mountains, Egypt). (November 2015) - Schmidt, Christoph; Kindermann, Karin; van Peer, Philip; Bubenzer, Olaf
Abstract: Sodmein Cave in Egypt is one of the rare archaeological sites in north-eastern Africa conserving human occupation remains of a period most relevant for the 'Out of Africa II' hypothesis. This underlines the need for establishing a chronological framework for the more than 4 m of stratified sediments ranging from the Middle Stone Age (MSA) to the Neolithic. The lowest layer J hosts huge fireplaces, from which we report luminescence ages of heated chert fragments unearthed from different depths. The 'multi-emission' dating approach – using both the blue and red TL of each specimen as well as the OSL emission of one sample – allowed identifying the most reliable ages. Samples yield ages between <121 ± 15 ka (maximum age) and 87 ± 9 ka. These data evidence human presence at the site during MIS 5. For integrating Sodmein Cave into the actual discussion of the dispersal patterns of modern humans and to identify potential connections with other sites in the Nile Valley and in the Middle East, a sound and reliable chronology is indispensable. Highlights: We present new luminescence ages for this Middle Stone Age sequence. Multi-emission dating of heated chert allowed selecting the most reliable ages. The ages prove human occupancy during MIS 5. The new data suggest a use and re-use of the fire pit during a prolonged period.